Screening of chitinase production medium by Fusarium solani isolated from endophytic karst using Two Level Factorial Design - Musdalifah, Musdalifah; Rachmawaty, Rachmawaty; Alimuddin, Alimuddin; Pagarra, Halifah; Azis, Andi Asmawati; Masriany, Masriany (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2026)
Chitinase is an important enzyme in various biotechnology applications, especially in biological control, so it requires increased induction efficiency. This study aims to determine the growth media factors that most influence the production of chitinase enzymes by the endophytic fungus Fusarium solani using the 2-Level Fractional method. Eight media variables are estimated to have an effect, namely the content of chitin colloid, ammonium sulfate, potassium sodium tartrate, KH2PO4, Na2HPO4, MgSO4·7H2O, CaCl2, and pH. Chitinase activity was evaluated using the DNS technique after four days of liquid fermentation and analyzed using the design express DX6 4.1 application. The results of the analysis of variance (ANOVA) showed that the second-order polynomial regression model was very significant (p <0.0001), with an R² value of 0.9515, which indicates that the model explains 95.15% of the data variation. Based on the screening results, it was found that ammonium sulfate, Na2HPO4, and MgSO4 7H2 were the most effective in increasing chitinase production. Optimization of media conditions resulted in an increase in chitinase activity of up to 18 U/mL. This research has the potential to be used as a basis for developing industrial-scale bioprocesses for the formulation of chitinase-based biopesticides and biopharmaceutical products.